The taxonomic attribution of African hominin postcrania from the Miocene through the Pleistocene: Associations and assumptions. Issue 173 (December 2022) - Grine, Frederick E.; Mongle, Carrie S.; Fleagle, John G.; Hammond, Ashley S.
Abstract: Postcranial bones may provide valuable information about fossil taxa relating to their locomotor habits, manipulative abilities and body sizes. Distinctive features of the postcranial skeleton are sometimes noted in species diagnoses. Although numerous isolated postcranial fossils have become accepted by many workers as belonging to a particular species, it is worthwhile revisiting the evidence for each attribution before including them in comparative samples in relation to the descriptions of new fossils, functional analyses in relation to particular taxa, or in evolutionary contexts. Although some workers eschew the taxonomic attribution of postcranial fossils as being less important (or interesting) than interpreting their functional morphology, it is impossible to consider the evolution of functional anatomy in a taxonomic and phylogenetic vacuum. There are 21 widely recognized hominin taxa that have been described from sites in Africa dated from the Late Miocene to the Middle Pleistocene; postcranial elements have been attributed to 17 of these. The bones that have been thus assigned range from many parts of a skeleton to isolated elements. However, the extent to which postcranial material can be reliably attributed to a specific taxon varies considerably from site to site and species to species, and is often the subject of considerable debate. Here, we review the postcranial remains attributed to African hominin taxa from the Late Miocene to the Middle and Late Pleistocene and place these assignations into categories of reliability. The catalog of attributions presented here may serve as a guide for making taxonomic decisions in the future.